Management capability of Malay and bumiputera SMEs in Malaysia / Muhammad Rozi Malim - Malim, Muhammad Rozi; Shahibi, Mohd Sazili; Sidek, Abdul Halim; Daimin, Ghazali (Research Management Institute (RMI), 2013)
Management Capability has been an important indicator of performance in management. It indicates beyond the individual’s skill level to reflect the impact of these skills at organizational level. “Capability” is the ability to perform actions. As it applies to human capital, capability is the sum of expertise and capacity. It measures the application of management to the total organization and to the resulting organizational performance that is achieved. Excellent in management capability performance leads to sustainable performance and business growth. The interest in small and medium-sized enterprises (SMEs) has witnessed significant growth over the years. In Malaysia, SMEs operate in almost every major industry. Small business entrepreneurs operate and manage various businesses and contribute to the national economy. SMEs, especially the Malays, are often confronted with problems that are uncommon to the larger companies and multinational corporations. One of the major problems in SMEs is management skill. Improving the management skills of managers of SMEs contributes to their survival and growth. This study wishes to investigate the overall management capability of Malay SMEs. The main objective is to evaluate the management skills and competences of Malay SME managers in Malaysia using Management Capability Index (MCI). The MCI converts the evaluation of management performance of a manager into an index. The index then is a useful indicator of how capable or inadequate a Malay SME manager is against a set of predetermined criteria. Another objective is to identify all the Malay talents in Malay SMEs, and how they acquire their knowledge and skills. To realize the objectives, a survey will be conducted using comprehensive questionnaires. The questionnaires will be mailed out to at least 500 Malay SMEs at all over Peninsular Malaysia especially Klang Valley.